CLINICAL IMPLICATION OF FATTY ACID CHANGES IN PATIENTS WITH PRIMARY GOUT ASSOCIATED WITH ARTERIAL HYPERTENSION - N. N. Kushnarenko; A. V. Govorin (Рациональная фармакотерапия в кардиологии)
Aim. To study blood levels of non-esterified fatty acids (NEFAs) and adenyl nucleotides, and fatty acids levels in lipids of erythrocyte membranes in patients with primary gout associated with arterial hypertension (HT). Material and methods. 175 male patients with primary gout were included in the study. According to 24-hour blood pressure (BP) monitoring results patients were split into two groups: 74 patients with normal BP (group 1) and 101 patients with HT (group 2). 29 healthy age-comparable subjects were included into control group. Uric acid, total NEFAs and glycerol blood levels were studied in all patients. Adenyl nucleotides (ATP , ADP and AMP) levels were determined in erythrocytes. Higher fatty acid levels were specified in lipids of erythrocyte membranes, including the following acids: myristinic (С14:0), palmitinic (С16:0), stearic (С18:0), pentadecanic (С15:0), heptadecanic (С17:0), pentadecenic (С15:1), heptadecenic (С17:1), palmitooleic (С16:1), oleic (С18:1), linoleic (С18:2ω6), α-linolenic (С18:3ω3), γ-linolenic (С18:3ω6), dihomo-γ-linolenic (С20:3ω6), arachidonic (С20:4ω6), eicosapentaenoic (С20:5ω3), and docosapentaenoic (С22:5ω3). Results and discussion. Hypertensive patients with gout demonstrated higher NEFAs blood level and greater changes in ATP-ADP-AMP system than normotensive gout patients and healthy subjects as well as 2.2 and 3.7 times higher NEFAs/ATP ratio, respectively. In hypertensive patients with primary gout the composition of fatty acids in erythrocyte membranes lipids changed due to increase in saturated fatty acids amount and decrease in unsaturated fatty acids amount, at that monoenic acid levels increased while polyenic acid levels decreased in unsaturated acids composition. Hypertensive patients with gout shown 1.3 and 2.5 times less levels of ω-3 poly-unsaturated fatty acids (PUFA) than normotensive gout patients and healthy subjects, respectively. At the same time ω-6 PUFA levels changed in bidirectional manner: γ-linolenic and dihomo-γ-linolenic acids levels rose, while arachidonic acid amount was 1.2 and 2.3 times less in comparison with these in gout patients with normal BP and healthy subjects.  Conclusion. Study data demonstrate that fatty acid metabolic disturbances possibly contribute to HT development in patients with primary gout.